Uncharted territory: Universal credit, couples and money - Griffiths, R; Wood, M; Bennett, F; Millar, J (Institute of Policy Research, University of Bath, 2020)
This report presents findings from the first phase of the ESRC-funded project, ‘Couples balancing work, money and care: exploring the shifting landscape under Universal Credit’ – a three-year longitudinal, qualitative research study which examines the ways in which couples with and without children make decisions about work, care and household finances in relation to changes under Universal Credit.